IMPROVING JAPANESE SPEAKING SKILLS DURING PROSPECTIVE INTERNS: PICTURE AND PICTURE LEARNING MODEL - Hasibuan, Adriana; Pawiro, Muhammad Ali (Universitas Islam Sumatera Utara (UISU), 2025)
This study analyzes the speaking ability in Japanese by nurses who are engaged in prospective interns provided for them who will work in Japan through the EPA (Economic Partnership Agreement) program. The study involves 49 participants following the program and uses quantitative method as proposed by Brown Rodgers (2002). Being conducted with a training time of 15 hours for five days through classroom action, this study starts with planning, implementation, observation, and evaluation. Data collection methods include interviews, observations, pre-tests and post-tests. Written tests apply to see their ability to master Japanese grammar, and oral tests to measure Japanese speaking ability. The Picture and Picture learning model is aimed at improving the nurses’ mastery of Japanese vocabulary. To obtain such mastery the questions are formulated as the followings: how can an action plan improve participants’ speaking skills and what pedagogical implications are obtained by them? The results show that the action plan improves the participants’ speaking ability in Japanese. The pre-test results show that 15 of them (31%) are able to speak with some stuttering with an average score of 64.38 and the post-test results indicate an increase to 39 participants (79.6%) with an average score of 77.1. It is concluded that participants can construct ideas and thoughts orally; thus, the effective vocabulary of pictures and their interests implicate their pedagogical development to a better condition, so they are claimed to be ready to work in Japan.